Symmetry and non-existence of positive solutions for fractional p-Laplacian systems. (June 2019) - Chen, Yonggang; Liu, Baiyu
Abstract: Chen and Li (2018) developed maximum principles for the fractional p-Laplacian, which carry out the direct method of moving planes to the fractional p-Laplacian equation. In this paper, we generalize their method to the system case and obtain a symmetry result for the fractional p-Laplacian system on the whole space. We also consider the system on the upper half space and obtain a non-existence result.